What variables can differentiate winning and losing teams in the group and final stages of the 2018 FIFA World Cup? - Alves, D. L.; Osiecki, R.; Palumbo, D. P.; Moiano-Junior, J. V. M.; Oneda, G.; Cruz, R. (International Journal of Performance Analysis in Sport, 2019)
To compare the tactical, physical and technical indicators between winners and losers of the group and final stages of the 2018 FIFA World Cup (WC). Eighteen variables were analysed, divided into tactical (ball possession), physical (distance covered, sprints and intensity zones 1 [low] to 5 [high]) and technical indicators (passing, shots and corners). The losing teams had lower ball possession in the group stage when compared to the winners (p = .04). There was a tendency (p = .06) for winners to spend more time in high intensity (group stage). Winners also had a tendency towards greater passing success (p = .06), shots (p = .05) and shots on target (p < .01). In summary, the winning teams have greater ball possession and pass success during the group stage of the 2018 FIFA WC, in addition to spending more time at high intensities and achieving more shots and shots on target independent of whether the match was performed in the group or final knockout stage. Our findings do not suggest any additional physical, tactical or technical variable in the determination of success in high-level soccer competition.